FROST INVESTIGATION 1944-1945. APPENDIX 15. BIBLIOGRAPHY. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1945)
The bibliography is a reference to published articles on subject matter related to frost phenomena. Most of the publications listed have influenced the general development of laboratory and field procedures for frost investigations. (Author) See also Appendix 14, AD-712 472.